Phylogeographical analysis of two cold‐tolerant plants with disjunct Lusitanian distributions does not support in situ survival during the last glaciation - Gemma E. Beatty; Jim Provan (Journal of Biogeography, 2014)
Aim We used a combination of modelling and genetic approaches to investigate whether Pinguicula grandiflora and Saxifraga spathularis , two species that exhibit disjunct Lusitanian distributions, may have persisted through the Last Glacial Maximum ( LGM , c . 21 ka) in separate northern and southern refugia. Location Northern and eastern Spain and south‐western Ireland. Methods Palaeodistribution modelling using Maxent was used to identify putative refugial areas for both species at the LGM , as well as to estimate their distributions during the Last Interglacial ( LIG , c . 120 ka). Phylogeographical analysis of samples from across both species' ranges was carried out using one chloroplast and three nuclear loci for each species. Results The palaeodistribution models identified very limited suitable habitat for either species during the LIG , followed by expansion during the LGM . A single, large refugium across northern Spain and southern France was postulated for P. grandiflora . Two suitable regions were identified for S. spathularis : one in northern Spain, corresponding to the eastern part of the species' present‐day distribution in Iberia, and the other on the continental shelf off the west coast of Brittany, south of the limit of the British–Irish ice sheet. Phylogeographical analyses indicated extremely reduced levels of genetic diversity in Irish populations of P. grandiflora relative to those in mainland Europe, but comparable levels of diversity between Irish and mainland European populations of S. spathularis , including the occurrence of private hapotypes in both regions. Main conclusions Modelling and phylogeographical analyses indicate that P. grandiflora persisted through the LGM in a southern refugium, and achieved its current Irish distribution via northward dispersal after the retreat of the ice sheets. Although the results for S. spathularis are more equivocal, a similar recolonization scenario also seems the most likely explanation for the species' current distribution.